IMPACT OF STRESS ON FEMALE REPRODUCTIVE HEALTH: DISORDERS AND IMPLICATIONS - Ashurova, N.G.; Tolibov , F.F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The article examines contemporary aspects of stress-related diseases affecting the female reproductive system. It highlights that young women today experience the highest levels of stress, leading to conditions such as ovarian dysfunction, premenstrual tension syndrome, and benign mammary gland dysplasia. The mechanisms underlying these pathologies are discussed. Additionally, the article explores the effectiveness of long-term non-hormonal therapy using a standardized extract from Vitex agnus-castus (Ze440). It also considers the potential of a safe non-hormonal treatment for early menopausal symptoms based on Cimicifuga racemosa extract (Ze450), which aligns with treatment strategies for women experiencing menopausal disorders.